Owning a Dog as a Determinant of Physical Activity and Metabolic Control in Patients With Type 1 and Type 2 Diabetes Mellitus - Riske, Julia; Janert, Martin; Kahle-Stephan, Melanie; Nauck, Michael A. (Experimental and Clinical Endocrinology & Diabetes, 2019)
Background/aims Physical activity is recommended for patients with type 1 (T1D) and type 2 diabetes (T2D). We wanted to assess whether owning a dog influences duration or intensity of physical activity and metabolic control of diabetes mellitus.Patients and methods 143 patients with T1D (age 50±16 y.; BMI 25.7±4.5 kg/m2, HbA1c 8.6±1.6%) and 303 with T2D (age 63±11 y., BMI 33.7±7.3 kg/m2, HbA1c 9.0±1.6%, 232 [76.6%] insulin-treated, 89±61 IU/d), respectively, participated. A standardized questionnaire assessed diabetes history and treatment, details regarding time spent (per week) and intensity (MET, metabolic equivalent of task) of physical activity (“walking the dog” and other activities), anthropometric (BMI) and laboratory measures.Results 31.5% of T1D 23.1% of T2D patients were dog owners. Dog owners with T1D and T2D diabetes spent 19.0±3.3 and 19.8±2.6 MET.h per week walking the dog, which represented 61.3±5.7 and 62.9±4.9% of their total physical activity. Participants not owning a dog compensated by performing significantly more other activities. Taken together, total physical activity was similar in dog owners with T1D (p=0.80), but higher in dog owners with T2D (30.1±2.8 vs. 18.6±1.4 MET.h per week in those not owning a dog; p=0.0001). Body-mass-index or HbA1c were not significantly different in either patients with T1D or T2D either owning a dog or not.Conclusions Owning a dog motivates to a significant amount of physical activity, but this was fully compensated for by other forms of physical activity in (younger) patients with T1D. Even the higher physical activity in dog owners with T2D did not result in improved glycaemic or body weight control.